HUBUNGAN KEKERABATAN IPOMOEA TRIFIDA (H.B.K.) G. DON ASAL CITATAH JAWA BARAT BERDASARKAN KARAKTER MORFOLOGI POLEN - Tia Setiawati; Budi Irawan; Nisa Hurin (JURNAL ISTEK, 2015)
The purpose of this study was to determine the relationship of kindship 30 accessions of Ipomoea trifida origin Citatah West Java based on morphological characters of pollen which includes shape, size, type of aperture, and ornamentation of exine. Preparation of pollen carried out using the Erdtman (1966) method. The result shows that the shape of pollen I.trifida are rounded (oblate spheroideal and prolate spheroideal with the ratio P / E : 7 / 8-8 / 8 & 8 / 8-8 / 7), pollen grain size is medium (25-50 µm), type of aperture is porous and exine ornamentation is echinet with variations blunt end and a pointed tip. Analysis of pollen morphological characters using NTSYSpc program version 2.0 produces dendogram that divide 30 accession I.trifida into two branches. The first branch consisted of 21 accessions are accession no. 69, 151, 166, 178, 94, 179, 108, 132, 111, 145, 147, 168, 214, 215, 158, 199, 201, 216, 212, 170 and 171. The second branch consists of 9 accessions are accession no. 109, 167, 187, 180, 209, 177, 196, 197 and 113.